Dynamic simulation of the tractor HMCVT under typical working conditions based on AMESim - Xiao, Maohua; Zhao, Yuanfang; Li, Xianhua; Hussain, Ghulam; Wang, Shengjie; Zhu, Yejun (International Journal of Agricultural and Biological Engineering, 2022)
In order to study the dynamic characteristics of hydro-mechanical continuously variable transmission (HMCVT) under ploughing and sowing conditions, a complete simulation model of HMCVT is established based on AMESim software, including mechanical transmission model, pump controlled hydraulic motor speed control model and section changing hydraulic system model. In addition, the dynamic model of tractor is established. In order to verify the correctness of the simulation model, a test-bed is established. The test of tractor running speed and the test of pump controlled hydraulic motor system were carried out on the test-bed. The test results show that the simulation model of pump control hydraulic system can correctly reflect the change of transmission ratio of pump controlled hydraulic motor, and the simulation model can reflect the actual working condition change of clutch. Thus, the correctness of the previous simulation model based on AMESim is verified. Based on the simulation model established by AMESim, the dynamic characteristics of HMCVT under ploughing and sowing conditions are studied. The results show that: Under ploughing condition, the planetary platoon will have strong impact at the moment of throttle opening and changing section. Under sowing condition, the HMCVT will have a great impact at the time of variable cross section, but the variation range of rodent force decreases and the change trend tends to be stable.Keywords: tractor, HMCVT, AMESim, dynamics simulation, testDOI: 10.25165/j.ijabe.20221502.6815Citation: Xiao M H, Zhao Y F, Li X H, Hussain G, Wang S J, Zhu Y J. Dynamic simulation of the tractor HMCVT under typical working conditions based on AMESim. Int J Agric & Biol Eng, 2022; 15(2): 102–110.